Sistema integrado de gestão para pequenas empresas de serviços - Schefer, Fabiano (2007)
This paper shows a study about the main management systems currently applied by the Brazilian companies, presenting particular features and some common aspects which allow the integration of the ISO 9001, National Prize of Quality and Strategic Planning. Thus, a gathering system of management has been idealized and developed around the strategic control originated by the pointers intersection and optimized by the Balanced Scorecard selected by a service rendered company on management technologies according to the necessities originated by such systems demands and by the own directory of the organization. The study, however, does not aim at presenting the whole documentation generated and applied by the company on the construction of the gathering system, but the tools built for that and the pointers matrix belonging to the center of the study. The results achieved showed to be effective for the obtaining a multifunctional system composed by 45 pointers, and of small associated documentation, versatility on the new systems gathering, superior performances to the established aim, besides multiple external conquests such as the Prêmio Qualidade RS (Silver Trophy category), and the ISO 9001 certification. Starting from that, we expect other organizations develop their management systems based on the measurement system, motivated by the simple method developed in this work and of great outcome in order to better administrate their business and also to enlarge the resources invested in their administration